2019
DOI: 10.1111/bpa.12731
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and activation of colony‐stimulating factor 1 receptor in the SIV/macaque model of HIV infection and neuroHIV

Abstract: In the present study, we investigated whether colony‐stimulating factor 1 receptor (CSF1R) is expressed on brain macrophages and microglia in the human and macaque brain and whether it is upregulated and activated after lentivirus infection in vivo and contributes to development of encephalitic lesions. We examined, using multi‐label and semi‐quantitative immunofluorescence microscopy, the protein expression level and cellular localization of CSF1R in brain tissues from uninfected controls and SIV‐infected adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…CSF1 is a cytokine of the mononuclear phagocytic system that is upregulated in a variety of CNS diseases, such as AD [46], EAE [47], and neuro HIV [23]. The biological effects of CSF1 are mediated by CSF1R, which is crucial in promoting the migration, proliferation, differentiation, survival, and polarization of macrophagelineage cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSF1 is a cytokine of the mononuclear phagocytic system that is upregulated in a variety of CNS diseases, such as AD [46], EAE [47], and neuro HIV [23]. The biological effects of CSF1 are mediated by CSF1R, which is crucial in promoting the migration, proliferation, differentiation, survival, and polarization of macrophagelineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…CSF1R is essential for microglia viability [15,20], which not only regulates the development, proliferation, and maintenance of microglia but also plays a major role in neuroinflammation [21,22]. Moreover, the expression and activity of CSF1R are increased after brain damage [15,23]. Wlodarczyk et al reported that stimulation of CSF1R by recombinant mouse CSF1 could induce the expansion of CD11c positive microglia, leading to improvement of EAE symptoms and less demyelination [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several potential targets and approaches have been investigated by NIMH supported investigators to eliminate myeloid reservoirs. Irons et al 72 . demonstrated colocalization of CSF1R and its ligand CSF1 in perivascular macrophages in the brains of encephalitic macaques and humans (virally suppressed).…”
Section: Strategies For Cure: Eradication Controlmentioning
confidence: 99%
“…Several potential targets and approaches have been investigated by NIMH supported investigators to eliminate myeloid reservoirs. Irons et al 72 demonstrated colocalization of CSF1R and its ligand CSF1 in perivascular macrophages in the brains of encephalitic macaques and humans (virally suppressed). These findings point to opportunities for developing a specific approach, targeting infected brain macrophages, with several brain penetrant CSF1R inhibitors that are available now, to eliminate central nervous system macrophage reservoirs.…”
Section: Strategies For Cure: Eradication Controlmentioning
confidence: 99%
See 1 more Smart Citation